The interRAI Child and Youth Suite of Mental Health Assessment Instruments: An Integrated Approach to Mental Health Service Delivery - Stewart, Shannon L.; Celebre, Angela; Semovski, Valbona; Hirdes, John P.; Vadeboncoeur, Chris; Poss, Jeffrey W. (Frontiers in Psychiatry, 2022)
Various biological, social, psychological, and environmental factors impact children and youth living with mental health problems across their lifespan. To meet the wide-ranging challenges of mental illness, service system integration is needed to improve efficiencies and reduce fragmentation. Unfortunately, the mental health system has been plagued by the lack of coordination across services. There is a general consensus that mental health service delivery must ensure a child or youth’s needs are addressed in a collaborative, coordinated, and seamless manner. A key element to successful integration is the development of a comprehensive standardized screening and assessment system. Numerous assessments have been developed to assess child mental health and functioning, but they typically have a very narrow focus with limited use and utility. Not only does this reduce the ability to take a life course perspective to mental health, but this uncoordinated approach also results in redundancies in information collected, additional resources, and increased assessor burden for children, youth, and their families. The interRAI child and youth mental health assessment suite was developed in response to the need for an integrated mental health system for young persons. This suite includes screening and assessment instruments for in-patient and community settings, emergency departments, educational settings, and youth justice custodial facilities. The instruments form a mental health information system intentionally designed to work in an integrated fashion beginning in infancy, and incorporate key applications such as care planning, outcome measurement, resource allocation, and quality improvement. The design of these assessment tools and their psychometric properties are reviewed. Data is then presented using examples related to interpersonal trauma, illustrating the use and utility of the integrated suite, along with the various applications of these assessment systems.